Pelatihan Penguatan Literasi Hukum dan Numerasi dalam Implementasi Kurikulum Merdeka di MI Nurul Huda Jelu Kecamatan Ngasem Bojonegoro - Lisa Aminatul Mukaromah; Midya Yuli Amreta; Khurul Anam; Siti Nur Hamidah; Nuslul Arum Ningtyas; Taqwi Matus Sholikhah; Humai Rosyaida (I-Com: Indonesian Community Journal, 2025)
ABSTRAK The legal literacy and numeracy literacy skills of students at MI Nurul Huda Jelu still need to be improved. One of the contributing factors is the inability of teachers to integrate these optimally. This study aims to implement strengthening training in order to support the implementation of the Merdeka Curriculum at MI Nurul Huda Jelu. This training is aimed at improving teachers' abilities in integrating legal literacy and numeracy in the classroom learning process. Data were collected through interviews, observations, and documentation. The evaluation of this training is in the form of a test sheet. The results of the question training show that the abilities of students, with an average score of students in the legal literacy question training being 93, while in the numeracy literacy work the average score of students was 56. Students and teachers who take part in this training are expected to be able to compile and implement more contextual and relevant learning according to the needs of students. The suggestion from this community service activity is that teachers are consistently expected to apply and integrate learning with the legal literacy system and numeracy literacy in the learning process. Kata kunci: Literacy, law, numeracy, idependent kurikulum